The ethical structure of production - Wiśniewski, Jakub Bożydar (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The main contention of the present paper is that the capital structure of production, the preservation of which is often regarded as the essence of economic sustainability, needs to be grounded in the parallelethical structure of production in order to remain intact. The article identifies several tendencies conducive to the erosion of the ethical production structure. Subsequently, it suggests that some of these tendencies may well be strongly present in today’s economic and cultural climate in the so-called developed world, thereby jeopardizing its prospects for continued economic growth and progress. Finally, the author indicates that only a widespread and well-established understanding of the relationship between the capital structure of production and its ethical counterpart can preventa retrogression from the current, historically unprecedented level of global economic well-being.
Keywords: economics and ethics; cultural economics; ethical capital; economic development; soft institutions